THE INFLUENCE OF INNOVATIVE-PARADIGMAL APPROACHES TO THE IMPLEMENTATION OF PEDAGOGICAL CONDITIONS IN THE PROFESSIONAL TRAINING OF FUTURE OFFICERS IN THE HIGHER MILITARY EDUCATIONAL INSTITUTIONS - RUDYNSKYI, Vitalii (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Abstract. The research raised the topical issue of the impact of innovative-paradigmatic approaches to the implementing pedagogical conditions in the professional training of future officers at the Military Academy (a higher military educational institution), based on the materials of the scientific works of Ukrainian scientists. The specified problem is not sufficiently covered in the modern scientific discourse; therefore, it needs deep analysis, detailing and coverage. It is noted that the teachers' use of innovative paradigmatic approaches to the military education system helps to establish the professionalism of the cadets, and affects their self-improvement and the acquisition of professional competence by future masters of military administration. The main approaches are defined and characterized: systemic, competence-based, person-oriented, creative, anthropological, cultural, sociological, informational and technological; their impact on improving the educational and professional training of future military specialists at the HMEI is considered. The levels of competence formation (diagnostic, political, technological and digital competence) are described. Their acquisition by cadets constitutes an individual ability to make balanced decisions and to convey one's vision to the assigned personnel. It is substantiated that innovative-paradigmatic approaches contribute to implementing pedagogical conditions in higher education institutions, which are divided into general and specific ones according to the object of influence. Pedagogical conditions are considered a properly created pedagogical environment (appears, exists and is always being improved), where the readiness of students to work in their profession is formed. Pedagogical conditions influence the development of subjects of study, their upbringing and educational level; and influence the dynamics of these processes and final results. Four pedagogical conditions that effectively influence the formation of the readiness of future officers to carry out successful professional activities are highlighted - the creation of a motivational and valuable educational environment in the process of learning academic disciplines, the deepening of the system of knowledge about the essence and mechanisms of the management of the SAS troops, supplementing the educational process with sustainable communicative and managerial interaction , implementation of means of actualization of self-development and self-improvement), each of which is meaningfully characterized and described.